Antecedents of Customers Loyalty towards Go-Jek Service - Helmy Ilham Nugraha; Anas Hidayat; Putra Endi Catyanadika; Sri Rejeki Ekasasi (Telaah Bisnis, 2021)
Service quality is one of the biggest factors in determining consumer loyalty. The aim of this study is to analyze how the Go-Jek service quality an influence customer satisfaction in shaping customer loyalty to the Go-Jek company. This research is quantitative and the variables examined in this study are website design, reliability, trust, customer satisfaction, to support consumer loyalty. This research was conducted in Yogyakarta and the data was collected using a questionnaire based on a Likert-scale, and the taking method uses purposive sampling with 300 respondents. Data were then analyzed using structural equation model (SEM) analysis with the help of WarpPLS software. The results of the study show that the effect of e-service quality on customer loyalty to the Go-Jek company were positive and significant.